(untitled) (World of finance, 2020)
Introduction. In the context of budget decentralization in Ukraine, local governments are trying to make effective use of their powers and financial potential of the territorial community in order to increase local budget revenues and funding of services at the local level. The purpose is to find out the essence of the financial potential of territorial communities and to analyze its current state in the context of existing and potential sources of financial resources that can be used by local governments for the realization of their goals and perspectives. Methods. To achieve goal, a system of general scientific and special methods of research was used: analysis, synthesis and generalization - in the processing of literary, statistical, legislative and Internet sources on the topic of research; methods of systematizing and generalizing data, comparing and detailing were used when conducting analysis of local budget revenues; graphical, tabular and visualization methods were used for visual representation of the processed data; abstract-logical method was used for summarize the material presented and formulate conclusions. Results. It has been found out that financial potential of a local community is a collection of available and potential sources of financial resources that local governments can attract through budgetary, investment, credit and grant mechanisms to ensure the effective functioning of the community. It is proved that budgetary funds is gradually increasing and prevail in the structure of financial resources of local self-government bodies in Ukraine. Despite the positive dynamics, local budget revenues have not yet become the basis of financial independence of territorial communities, and tax revenues make up 88% of the structure of local budget own revenues. Possibilities of attracting private sector investment funds on the basis of public-private partnership as a potential source of financial resources of territorial communities are analyzed. It has been found out that the sources of growth of the financial potential of local self-government are credits and grants, which provide financing for infrastructure projects for the development of territorial communities. It is proved that the specific reserve of resource provision of territorial communities is human capital, with the participation of which the formation, distribution and use of financial resources of the community takes place. Emphasis is placed on revenues from the disposal of municipal waste as an inexhaustible financial resource of territorial communities. Proposals for increasing the efficiency of utilization of the financial potential of territorial communities at the present stage of development have been developed. Conclusions. The subject of further scientific exploration is the search for and in-depth study of ways to effectively use the financial potential of local communities to improve the quality and accessibility of public services at the local level.